Aulin V.V., Slon V.V., Lysenko S.V. The variation of characteristics tribotechnical conjugations diesels with their work in different modes. - Аулін, В.В.; Слонь, В.В.; Лисенко, С.В. (Problems of Tribology, 2014)
The article describes the effects of various additives to replace the friction torque coupled models "roller-block" base lubricants and motor oils compositional M10Г2к on the friction machine СМЦ-2. Studies conducted in a continuous and "start-stop" mode. We found that the addition of additives "Ниод-5", "Roil Gold", "КГМТ-1" to the motor oil M10Г2к reduced level and the peak width of the first friction torque range and lower peak friction torque test on the remaining intervals. Found that the friction factor conjugate samples and components that run on motor oil M10Г2к can be handled and worn motor oil – restore it at modifying additive.